Analysis Of The Relationship Between Risk Factors Hemorrhoids In Pregnant Women In Sinjai District - M. Raihan Nabil Hadinata; Anna Sari Dewi; Sigit Dwi Pramono; M. Hamsah; Berry Erida Hasbi (Jurnal EduHealth, 2025)
Pregnancy often causes various changes in a woman's body , one of which is hemorrhoids , which generally occur in the second and third trimesters . This study aims to analyze the relationship between risk factors such as trimester of pregnancy , defecation position , and constipation with the incidence of hemorrhoids in pregnancy women in Sinjai Regency. The method used is an analytical observational approach with a case-control design at the Restu Ibu Maternity Clinic , with the case group consisting of pregnant women who experienced hemorrhoids and a control group who did not experience them . Data collection was carried out through medical records and direct interviews , and statistical analysis using the Chi- square test . The results showed that constipation had been significant relationship with the incidence of hemorrhoids (p = 0.003), while parity and defecation position factors did not show a significant relationship . This study suggests that constipation management should be the main step in preventing hemorrhoids in pregnancy women , as well as providing important insights for health workers and the community to increase awareness of hemorrhoid prevention during pregnancy .